New (alternative) temozolomide regimens for the treatment of glioma - Wolfgang Wick; Michael Platten; Michael Weller (2008)
One barrier to successful treatment of malignant glioma is resistance to alkylating agents such as temozolomide. The cytotoxic activity of temozolomide and other alkylating agents is believed to manifest largely by the formation of O(6)-methylguanine DNA adducts. Consequently, the primary mechanism of resistance to temozolomide is a function of the activity of the DNA repair enzyme O(6)-methylguanine DNA methyltransferase (MGMT). Fortuitously, MGMT is inactivated after each reaction (i.e., suicide enzyme). Therefore, if the rate of DNA alkylation were to outpace the rate of MGMT protein synthesis, the enzyme could, in theory, be depleted. Several studies have shown that prolonged exposure to temozolomide can deplete MGMT activity in blood cells, a process that could potentially increase the antitumor activity of the drug. To date, however, there are limited data demonstrating the depletion of MGMT activity in tumor tissue exposed to temozolomide. A variety of dosing schedules that increase the duration of exposure and the cumulative dose of temozolomide are currently being investigated for the treatment of glioma, with the goal of improving antitumor activity and overcoming resistance. These alternative dosing regimens have been shown to deplete MGMT activity in peripheral blood mononuclear cells, but the regimen that provides the best balance between enhanced antitumor activity and acceptable hematologic toxicity has yet to be determined.